ミズホ コウゲン ニオケル セッピョウガク テキ ケンキュウ ノ セイカ ノ ガイヨウ ダイ1カイ ナンキョク キスイケン シンポジウム - 石田, 完; イシダ, タモツ; ISHIDA, Tamotsu (国立極地研究所, 1979)
P(論文) 1969-1975年に実施された「みすほ高原における雪氷学的研究」の成果は,国立極地研究所発行のMemoirs of National Institute of Polar Research, Special Issue No 7 (1978)に発表されたが,ここてはその概要を述べ,今後に残された問題点にもふれた. A summary report of the traverse glaciology proiect accomplished by the Japanese Antarctic Research Expedition in 1969-1975 was published in 1978 under the title of "Glaciological Studies in Mizuho Plateau, East Antarctica, 1969- 1975" as a special issue of Memoirs of National Institute of Polar Research, No 7 This paper outlines the abovementioned summary report departmental bulletin paper